2013
DOI: 10.1167/13.13.18
|View full text |Cite
|
Sign up to set email alerts
|

Microsaccades are modulated by both attentional demands of a visual discrimination task and background noise

Abstract: Microsaccades are miniature saccades occurring once or twice per second during visual fixation. While microsaccades and saccades share similarities at the oculomotor level, the functional roles of microsaccades are still debated. In this study, we examined the hypothesis that the microsaccadic activity is affected by the type of noisy background during the execution of a particular discrimination task. Human subjects had to judge the orientation of a tilted stimulus embedded in static or dynamic backgrounds in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 39 publications
4
28
0
Order By: Relevance
“…In humans, it was reported that microsaccade activities were influenced by the attentional load in visual tasks 9 , 23 , 24 or nonvisual cognitive tasks 25 29 , such as arithmetic operation and digit retention, in which the primary mental process does not rely on vision. However, previous research investigating the relationship between the attentional load and the microsaccade rate obtained inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, it was reported that microsaccade activities were influenced by the attentional load in visual tasks 9 , 23 , 24 or nonvisual cognitive tasks 25 29 , such as arithmetic operation and digit retention, in which the primary mental process does not rely on vision. However, previous research investigating the relationship between the attentional load and the microsaccade rate obtained inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…Hicheur et al . 24 employed a forced choice-task paradigm in which participants had to judge the orientation of a titled stimulus embedded in static or dynamic backgrounds. They found significantly higher microsaccade rate when participants were engaged in the execution of the discrimination task (high load) compared to that when they did not need to make response (low load).…”
Section: Introductionmentioning
confidence: 99%
“…When looking at the spatio-temporal details, the eyes also continuously perform what is called fixational eye movements, which are a combination of drifts, tremors, and micro-saccades. While the role of saccades to explore the visual environment and foveate stimuli of interest has been previously discussed, micro-saccades may similarly contribute to active vision at a different scale (Hicheur, Zozor, Campagne, & Chauvin, 2013). The neural and functional segregation of the different types of eye movements is debated, and it has been argued that common neural mechanisms may underly saccades and micro-saccades generation (Krauzlis, Goffart, & Hafed, 2017;Otero-Millan, Troncoso, Macknik, Serrano-Pedraza, & Martinez-Conde, 2008).…”
Section: Visual Perceptionmentioning
confidence: 99%
“…More careful testing would be required to conclude on this part, but they may also contribute to increase the acuity of the system (see Ko, Poletti, and Rucci (2010) for related human experiments; Franceschini, Chagneux, Kirschfeldand, and Mcke (1991) for early experiments in the fly; Viollet (2014) for a review of visual sensors hyperacuity based on micro-eye movements). They may also contribute to cognitive demands at end (Hicheur et al, 2013) through the activation of task-dependent projections. Generalizing to other movements and equilibriums, a connection can be made with the slight and chaotic movements performed by the human body for keeping balance (Milton, Insperger, & Stepan, 2015).…”
Section: Fixational Eye-movementsmentioning
confidence: 99%
“…There has been little research looking specifically at saccadic measures in DOC, except for quick saccadic oscillations (39). Microsaccades (small involuntary jerks of the eye) may be useful as an alternative for eye movement assessment of visual attention in the future (4850), but their role in DOC, if any, have yet to be established.…”
Section: Reviewmentioning
confidence: 99%